Daughters - Marshall, Paule 1929-2019 (A Plume book, 1992)
"At its center is Ursa Beatrice MacKenzie, a well-educated, good-hearted young black woman who is struggling to make a career and life for herself in New York. But swirling around her are several crises, including an abortion, a decision to break up with her boyfriend, the start of a new job, and finally, the need to come to terms with her family back home, her father, a crusading politician known as the PM, and her mother, Estelle, a former teacher from Hartford." -- Back cover.